Antibacterial effects of adipose mesenchymal stromal cell-derived exosomes in vitro and in an Escherichia coli-induced acute lung injury mouse model - Jonnalagadda, Naveen (Kansas State University, 2021)
Antibacterial effects and immunomodulatory properties of mesenchymal stromal cells (MSCs) and their secretome are an emerging area of research. The antibacterial effects of MSC-derived secretome are attributed to antimicrobial peptides, and later speculated that these antimicrobial peptides were packaged within exosomes. It is also shown that, stimulation of MSCs with polyinosinic:polycytidylic acid (poly I:C), a toll-like receptor 3 (TLR 3) agonist, enhanced the antimicrobial and immunomodulatory properties and therapeutic effects. Exosomes, MSC-derived bilipid layered and nanosized secretome components, are shown to have immunomodulatory properties similar to MSCs. We hypothesized that exosomes derived from MSC have similar antibacterial activities as MSCs alone. In this study, we evaluated antibacterial effects of equine adipose MSC (ASC)-derived exosomes against Gram negative (Escherichia coli and Klebsiella pneumoniae) and Gram positive (Staphylococcus aureus and Rhodococcus equi) bacteria and investigated whether TLR 3 agonist stimulated ASC-derived exosomes enhanced the antibacterial activity. The therapeutic efficacy of ASC-derived exosomes was investigated in an Escherichia coli-induced acute lung injury mouse model. Equine ASCs were isolated and cultured in low-glucose DMEM medium containing 10% fetal bovine serum. Adipose stromal cells were stimulated with TLR 3 agonist (poly I:C) at 10 µg/ml concentration for 24 hours and exosomes were collected from both TLR 3 agonist stimulated and non-stimulated ASCs by differential ultracentrifugation. Characterization and quantification of exosomes were done by transmission electron microscopy, nanoparticle tracking analysis and bicinchoninic acid (BCA) protein assay. The in vitro antibacterial effects were determined by culturing bacteria with and without ASCs and ASC-derived exosomes, stimulated or non-stimulated by TLR 3 agonist and bacterial growth was assessed by measuring optical density at 0, 12, and 24-hour incubations and by determining bacterial cell concentration at 24 hours by spread plate method. An acute lung injury mouse model elicited by intratracheal injection of E. coli to evaluate the therapeutic efficacy of ASC-derived MSC exosomes. Bronchoalveolar lavage (BAL) fluid was collected for assessment of bacterial load and alveolar protein permeability. In vitro, ASCs and ASC-derived exosomes significantly inhibited growth of both Gram negative and Gram-positive bacterial species. Adipose MSC-derived exosomes showed a dose-dependent inhibition of bacterial growth. Toll-like receptor 3 stimulated ASCs enhanced the number of exosomes released by two-fold. In addition, TLR 3 stimulated ASCs and ASC-derived exosomes showed significant bacterial inhibition compared to the control groups. In the mouse model, ASCs and ASC-derived exosomes enhanced the bacterial clearance and alveolar permeability. In summary, ASC exosomes exhibited antibacterial activities similar to ASCs in both in vitro and in vivo. Both ASCs and ASC-derived exosomes exhibited antibacterial effects in a dose-dependent manner. This is the first study to demonstrate the antibacterial activities of MSC-derived exosomes in vitro against Gram negative and Gram-positive bacteria, and in vivo in a mouse acute lung injury model.
Keywords: Mesenchymal stromal cells; Adipose tissue; Exosomes; Antibacterial effects; Acute lung injury; Toll-like receptor 3 stimulation